2011
DOI: 10.1111/j.1399-0004.2011.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

CHD7 mutations causing CHARGE syndrome are predominantly of paternal origin

Abstract: CHARGE (coloboma, heart defects, atresia of the choanae, retarded growth and development, genital hypoplasia, ear anomalies and deafness) syndrome is a congenital malformation syndrome caused by mutations in the CHD7 gene in approximately 2/3 of cases. In the vast majority of cases, CHARGE syndrome is sporadic. There are only a few reports of parent-to-child transmission and somatic or gonadal mosaicism. To determine the parental origin of CHD7 mutations in sporadic CHARGE syndrome, we screened 30 families for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
11
1
1
Order By: Relevance
“…4 and Table 1). These findings contrast previously reported CHARGEcausing variants that are typically de novo and show a preference for paternal inheritance (23). Segregation analysis also showed that the discovered CHD7 alleles are not sufficient to explain the observed phenotypes (Fig.…”
Section: Deleterious Chd7 Missense Variants Cause Both Ks and Nigd Wicontrasting
confidence: 92%
See 1 more Smart Citation
“…4 and Table 1). These findings contrast previously reported CHARGEcausing variants that are typically de novo and show a preference for paternal inheritance (23). Segregation analysis also showed that the discovered CHD7 alleles are not sufficient to explain the observed phenotypes (Fig.…”
Section: Deleterious Chd7 Missense Variants Cause Both Ks and Nigd Wicontrasting
confidence: 92%
“…To date, only a few cases of parent-to-child transmission have been reported in CHARGE pedigrees with CHD7 mutation (23,25). In addition, over 80% of CHARGE-causing CHD7 mutations are null alleles (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the de novo and paternal origin of mutations associated with severe CHARGE (Pauli et al 2012), the vast majority of IHH-associated CHD7 variants is inherited, often from unaffected parents, and exhibit no apparent parent of origin bias (Balasubramanian et al 2014). In addition, in reports where segregation analysis of CHD7 missense alleles is available, there is considerable incomplete penetrance for the IHH phenotype in those harboring CHD7 missense mutations (Marcos et al 2014; Balasubramanian et al 2014).…”
Section: Missense Allelic Variants In Chd7 Can Cause Ihh In the Absenmentioning
confidence: 99%
“…In this article, we give an overview of all CHD7 missense variants reported in the literature before 15 June 2011 [Asakura et al, 2008;Bartels et al, 2010;Bergman et al, 2011a, b;Dauber et al, 2010;De Arriba Munoz et al, 2011;Delahaye et al, 2007;Felix et al, 2006;Feret et al, 2010;Fujita et al, 2009;Gao et al, 2007;Holak et al, 2008;Jongmans et al, 2006Jongmans et al, , 2008Jongmans et al, , 2009Kim et al, 2008;Lalani et al, 2006;Pauli et al, 2012;Vissers et al, 2004;Vuorela et al, 2007;Wessels et al, 2010;Wincent et al, 2008] and the variants that were reported in the NCBI Single Nucleotide Polymorphism database (http://www.ncbi.nlm.nih.gov/SNP, dbSNP build 132) with frequency data (n = 104, Supp. Table S1).…”
Section: Inclusion Of Chd7 Missense Variantsmentioning
confidence: 99%